Educational needs assessment and the management of chronic kidney disease in a Malaysian setting: a review - Sowtali, Siti Noorkhairina; Ghazali, Norhasyimah; Ishak, Nur ‘Ain; Draman, Che Rosle; Shah, Mohd Azarisman (IIUM Press, 2018)
Chronic kidney disease is among the top ten causes of mortality in Malaysia. An increase in the pattern of dialysis recipients has been observed, rising from 325 per million population in 2001 to 762 per million population in 2010. Chronic kidney disease is characterised by irreversible loss of renal function for at least three months, and the risk factors for chronic kidney disease include diabetes mellitus, hyperten-sion, cardiovascular disease, dyslipidaemia, and lifestyle risk factors such as poor dietary patterns, lack of exercise or physical activity, smoking, and increased alcohol intake. Thus, appropriate educational needs assessment is required to begin modifying these risk factors via educational intervention to delay disease progress and to prevent patients reaching end stage renal failure. The aim of this article is to provide a review of the existing literature on the chronic kidney disease process, based on recommended primary and secondary management from both medical aspects and lifestyle modification requirements, highlighting the importance of patient education.